Kepuasan Pasien Covid-19 terhadap Layanan Konseling Obat Jarak Jauh oleh Apoteker: Sebuah Studi Lintas Sektoral - Fonny Cokro; Yenni Ferlia; Hadiyanto Usman (Pengurus Pusat Ikatan Apoteker Indonesia, 2026)
Telemedicine has been used extensively since the COVID-19 pandemic. However, the non-face-to-face interactions make telemedicine services more challenging. This study was conducted to determine the satisfaction of drug counseling services provided by pharmacists through telemedicine in Jakarta, Indonesia, and to assess the correlation between the type of telemedicine and the provision of pharmacists’ drug counseling. This investigation is cross-sectional, and data were collected from February to May 2022 through Cluster and Snowball sampling methods. Chi-Square was used to measure the relationship between telemedicine models and the provision of drug counseling. Of the 448 respondents, 85.71% received counseling, giving the pharmacist's counseling performance a good value of 64.06-98.18%. More than 80% of respondents were satisfied in all aspects of satisfaction. The bivariate analysis shows a significant relationship between the type of telemedicine and drug counseling services (p=0.032). This research highlights the importance of optimizing telemedicine approaches to enhance patient care in pharmaceutical services.